1989
DOI: 10.1099/00221287-135-3-481
|View full text |Cite
|
Sign up to set email alerts
|

Production of Thiol-dependent Haemolysins by Listeria monocytogenes and Related Species

Abstract: Twenty-six strains belonging to the five main species of the genus Listeria were examined for production of thiol-dependent exotoxins. All strains of L. monocytogenes cultured in charcoal-treated broth secreted a haemolytic factor at a level ranging from 200 to 800 haemolytic units (HU) ml-1, except for the strain EGD (1500 HU ml-1) and the type strain CIP 82110T (10 HU ml-1). The haemolytic activity reached a maximum level by 8-10 h and then rapidly declined as soon as bacterial exponential growth ceased. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 17 publications
4
76
0
Order By: Relevance
“…A stock solution was prepared by dissolving 100 mg of eugenol in 10 mL of 95% ethanol. Aliquots were added to sterilized and cooled proteose peptone broth -PPG (Geoffroy et al, 1989) to give the final concentrations of 100, 300, 500, 800 and 1000 µg mL -1 . In order to detect the absence of antibacterial activity of ethanol, the experiments were performed with a control, with the solvent added to the medium.…”
Section: Determination Of Effect Of Eugenol Against L Monocytogenesmentioning
confidence: 99%
“…A stock solution was prepared by dissolving 100 mg of eugenol in 10 mL of 95% ethanol. Aliquots were added to sterilized and cooled proteose peptone broth -PPG (Geoffroy et al, 1989) to give the final concentrations of 100, 300, 500, 800 and 1000 µg mL -1 . In order to detect the absence of antibacterial activity of ethanol, the experiments were performed with a control, with the solvent added to the medium.…”
Section: Determination Of Effect Of Eugenol Against L Monocytogenesmentioning
confidence: 99%
“…These toxins include the species-specific types of Iisteriolysin 0 produced by the three Listeria species which are hemolytic on blood agar: Listeria monocytogenes (pathogenic for man anct animals), Listeria ivanoL·ii (animal pathogen) and Listeria seeligeri (apathogenic). Their Iisteriolysins have previously bet!n characterized biochemically [6,10],and it has also been shown that they vary in cytolytic activity.The gene for Iisteriolysin 0 (h/y) from 1.4. monocytogenes has been cloned and sequenced [4,13] and homologous DNA sequences have been detected in the chromosome of the two other hemolytic Listeria species [11]. lt has been firmly established, that Iisteriolysin 0 (LLO) is an essential virulence factor of L. monocytogenes (reviewed in Refs.…”
mentioning
confidence: 99%
“…These toxins include the species-specific types of Iisteriolysin 0 produced by the three Listeria species which are hemolytic on blood agar: Listeria monocytogenes (pathogenic for man anct animals), Listeria ivanoL·ii (animal pathogen) and Listeria seeligeri (apathogenic). Their Iisteriolysins have previously bet!n characterized biochemically [6,10],and it has also been shown that they vary in cytolytic activity.…”
mentioning
confidence: 99%
“…LLO is a virulence factor of LM and is essential for its escape from the phagocytic vesicle of the macrophage (1)(2)(3)(4)(5)(6). LLO, a member of the large family of CDCs, was first characterized by Geoffrey et al (7), and its pore-forming activity was shown to have a marked pH optimum. LLO exhibits very little cytolytic activity at neutral pH but substantial activity at pH Ͻ6.…”
mentioning
confidence: 99%